Identifying MMORPG Bots: A Traffic Analysis Approach. (8th October 2008) - Chen Chen, Kuan-Ta Kuan-Ta; Jiang Jiang, Jhih-Wei Jhih-Wei; Huang Huang, Polly Polly; Chu Chu, Hao-Hua Hao-Hua; Lei Lei, Chin-Laung Chin-Laung; Chen Chen, Wen-Chin Wen-Chin
Abstract : Massively multiplayer online role playing games (MMORPGs) have become extremely popular among network gamers. Despite their success, one of MMORPG's greatest challenges is the increasing use of game bots, that is, autoplaying game clients. The use of game bots is considered unsportsmanlike and is therefore forbidden. To keep games in order, game police, played by actual human players, often patrol game zones and question suspicious players. This practice, however, is labor-intensive and ineffective. To address this problem, we analyze the traffic generated by human players versus game bots and propose general solutions to identify game bots. Taking Ragnarok Online as our subject, we study the traffic generated by human players and game bots. We find that their traffic is distinguishable by 1) the regularity in the release time of client commands, 2) the trend and magnitude of traffic burstiness in multiple time scales, and 3) the sensitivity to different network conditions. Based on these findings, we propose four strategies and two ensemble schemes to identify bots. Finally, we discuss the robustness of the proposed methods against countermeasures of bot developers, and consider a number of possible ways to manage the increasingly serious bot problem.